2015
DOI: 10.1080/23273798.2015.1084012
|View full text |Cite
|
Sign up to set email alerts
|

World knowledge integration during second language comprehension

Abstract: In order to study the difficulties experienced during sentence comprehension in a foreign language (L2), we investigated semantic and world knowledge information retrieval in L2 comprehenders. Event-related potentials (ERP) were collected in late learners of English whose native language is Spanish, performing a sentence reading task in English. We investigated the mean amplitude of the P2 and N400 ERP components elicited by the critical word of sentences in three conditions: (1) correct; (2) semantic violatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Moreover, there have been studies not dealing with implicit causality which have shown that there is no delay in the influence of world knowledge and discourse context during processing, relative to the influence of lexical semantics (Hagoort, Hald, Bastiaansen, & Petersson, 2004; Nieuwland & Van Berkum, 2006). However, other studies have reported effects of lexical semantics that precede effects of world knowledge in sentence processing (Martin, Garcia, Breton, Thierry, & Costa, 2014, 2016), so the matter is still undecided.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, there have been studies not dealing with implicit causality which have shown that there is no delay in the influence of world knowledge and discourse context during processing, relative to the influence of lexical semantics (Hagoort, Hald, Bastiaansen, & Petersson, 2004; Nieuwland & Van Berkum, 2006). However, other studies have reported effects of lexical semantics that precede effects of world knowledge in sentence processing (Martin, Garcia, Breton, Thierry, & Costa, 2014, 2016), so the matter is still undecided.…”
Section: Introductionmentioning
confidence: 98%
“…The interpretation of an utterance therefore necessitates the simultaneous processing of various types of information such as semantics, syntax, world knowledge and the involvement of both working memory (WM) and long-term memory. Recent studies in second language (L2) have suggested that late L2 speakers sometimes have difficulties integrating multiple sources of information during online comprehension (Foucart, Moreno, Martin, & Costa, 2015;Foucart, Garcia, et al, 2015;Roberts, Gullberg, & Indefrey, 2008;Romero-Rivas et al, 2016; but see, Martin, Garcia, Breton, Thierry, & Costa, 2015). Most of these studies investigated processing at sentence level; in this paper we test whether these difficulties impair semantic processing during discourse comprehension.…”
Section: Introductionmentioning
confidence: 93%
“…These studies investigated whether L2 speakers take pragmatic information into account when incrementally processing a sentence and whether this affects their online interpretation of the message. More precisely, they looked at whether semantic processing is influenced by world knowledge violations (e.g., 'Mozart composed classic/jazz music'; Martin et al, 2015;Romero-Rivas et al, 2016), the speaker's identity ( e.g., 'Every night I drink a glass of wine', said by an adult or by a child; Foucart, Garcia, et al, 2015) or by one's own moral values ('Nowadays, paedophilia should be prohibited/tolerated across the world'; Foucart, Moreno, et al, 2015). In response to world knowledge violations, a similar N400 component was observed in native and L2 speakers (reflecting lexico-semantic integration difficulty; Kutas & Hillyard, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…How knowledge affects our comprehension of language has been extensively studied in the field of linguistics, particularly second language acquisition. In these studies, it can be observed that terms such as 'word knowledge' (Hagoort et al (2004), 'semantic knowledge' (Dascal, 2003), 'language knowledge' (Dudschig et al, 2016) are used interchangeably to define linguistic knowledge while 'world knowledge' (Dudschig et al, 2016;Martin et al, 2016;Gile, 1995), 'encyclopedic knowledge' (Setton,1999) and 'non-linguistic knowledge' (Dudschig et al, 2016;Setton,1999) are used to define extralinguistic knowledge. To better conceptualize these terms, 'linguistic knowledge' is defined as the knowledge obtained from previous experiences with language while 'extralinguistic knowledge' is defined as the knowledge obtained from previous experiences with the world.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, sentence comprehension in a foreign language is known to differ from native language comprehension (Martin et al, 2016: 207). A similar sentence violation method was used by Martin et al (2016) on L2 readers. The research group consisted of eighteen Spanish-English bilinguals who started to learn English as L2 at school age.…”
Section: Literature Reviewmentioning
confidence: 99%